Desarda technique versus Lichtenstein repair for inguinal hernia in tertiary care centre: a prospective study - Poojary, Harsha S.; Prasanna, Praveen Gudde; Mulki, Siddharth (International Surgery Journal, 2020)
Background: Various techniques for treatment of inguinal hernia have been studied. The use of a mesh is costly and has its own complications. In Desarda’s technique- external oblique muscle aponeurosis is placed in the form of an undetached strip for inguinal hernia repair. The objective of this study is to compare the outcomes of Lichtenstein’s repair versus Desarda’s technique. Methods: In this prospective study, 50 patients with inguinal hernia were enrolled at A. J. Institute of Medical Sciences and Research centre. 25 patients each were divided into two groups by randomization and were operated using Lichtenstein’s hernioplasty and Desarda’s technique. Patients were assessed for cost effectiveness, operation time, postoperative pain, hospital stay, foreign body sensation, return to non-strenuous activity, complications and recurrence rate in the postoperative period on day 1, 3, 5, 1 month and 6 months. Results: With regards to pain, foreign body sensation and duration of surgery Desarda’s repair was better than Lichtenstein’s repair (p<0.05). Mean hospital stay in Desarda’s group was comparable to the Lichtenstein group (p=0.16). Return to normal non-strenuous activity after 7-15 days in Desarda was 80% and 64% in Lichtenstein. No case of recurrence or chronic groin pain in either group was found. Conclusions: Based on the result, reduced cost of treatment, lesser post-operative pain and no mesh related complications authors can conclude that Desarda’s technique is equally effective as Lichtenstein’s repair for inguinal hernia and can consider it as the method of choice in treating inguinal hernia.